Endoscopic-assisted enucleation of radicular cysts - a case report - Abdullah, Kahairi; Ahmed Khan, Shamim; Ahmad, Amirozi (Universiti Sains Malaysia, 2010)
The standard management for the majority of benign jaw cysts is enucleation, marsupialisation, curettage and decompression. Enucleation has the advantage that the whole specimen is sent for microscopic evaluation so that more sinister pathological processes (i.e. squamous cell carcinoma) may not be missed. In a large cystic lesion, enucleation is still possible, but technical difficulties might be encountered. In such instances, inevitable damage can occur to the surrounding structures. We report a case of a large radicular cyst of the maxilla that was enucleated via endoscopic assistance through the Caldwell Luc approach.